2008
DOI: 10.1002/bit.21916
|View full text |Cite
|
Sign up to set email alerts
|

Improvements of enzyme activity and enantioselectivity via combined substrate engineering and covalent immobilization

Abstract: Esterases, lipases, and serine proteases have been applied as versatile biocatalysts for preparing a variety of chiral compounds in industry via the kinetic resolution of their racemates. In order to meet this requirement, three approaches of enzyme engineering, medium engineering, and substrate engineering are exploited to improve the enzyme activity and enantioselectivity. With the hydrolysis of (R,S)-mandelates in biphasic media consisting of isooctane and pH 6 buffer at 55 degrees C as the model system, th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
28
1

Year Published

2009
2009
2019
2019

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 36 publications
(31 citation statements)
references
References 57 publications
2
28
1
Order By: Relevance
“…However, the present hydrolases reported showed low activity and/or enantioselectivity towards (R,S)-CMM, which might be closely related with the sterically hindered 2-chlorophenyl moiety (Wang et al 2006b;Wang et al 2008). For example, the Candida antarctica lipase A catalyzed transesterification of (R,S)-CMM using vinyl propionate as an acyl donor with an enantiomeric ratio (E) of 34.7 (Uhm et al 2007).…”
Section: Introductionmentioning
confidence: 64%
See 2 more Smart Citations
“…However, the present hydrolases reported showed low activity and/or enantioselectivity towards (R,S)-CMM, which might be closely related with the sterically hindered 2-chlorophenyl moiety (Wang et al 2006b;Wang et al 2008). For example, the Candida antarctica lipase A catalyzed transesterification of (R,S)-CMM using vinyl propionate as an acyl donor with an enantiomeric ratio (E) of 34.7 (Uhm et al 2007).…”
Section: Introductionmentioning
confidence: 64%
“…In the present work, we aimed to develop an efficient strategy to improve the enantioselectivity of the existing enzymes towards (R,S)-CMM. It was reported that the 2-substituent of the acyl part strongly affected the rate-limiting formation or breakdown of the tetrahedral intermediate, and the stabilization of the transition state for the formation of the tetrahedral intermediate of the fast-reacting esters might increase the enzyme activity and enantioselectivity (Wang et al 2008). Therefore, herein, we speculated that the enzymatic enantioselectivity might be efficiently enhanced through manipulating the transition state by rational design.…”
Section: Introductionmentioning
confidence: 95%
See 1 more Smart Citation
“…Enzyme loading has been found to differ from enzyme to enzyme. For example, for lipase or penicillin acylase, enzyme loading was 100 mg/g 15) and 40 mg/g support 12) respectively. Compared with these two enzymes, the enzyme loading of BLAI was low, but was higher than that of penicillin V acylase (1 mg/g of support), 16) and was similar to that of glucose isomerase.…”
Section: Resultsmentioning
confidence: 99%
“…The good enthalpyentropy compensation relationships of DS R 5 2113. 5 . Thus, the entropic compensation effect is nearly negligible at 458C for obtaining an excellent CALB enantioselectivity.…”
Section: Thermodynamic Analysismentioning
confidence: 95%